PEMANFAATAN TEKNOLOGI DALAM RANGKA PENINGKATAN KOMPETENSI PEDAGOGIK - Noviyanti, Putu Ledyari; Patiung, Amos; Nababan, Siti Aminah; Tanjung, Henra Saputra; Nitiasih, Putu Kerti; Riastini, Putu Nanci; Sudatha, I Gde Wawan (MES: Journal of Mathematics Education and Science, 2024)
During the Industrial Revolution 4.0, it is important to develop critical thinking (Critical Pedagogy) and the use of technology in the learning process (Cyber Pedagogy). This research aims to explore how technology can be used to improve pedagogical competence in the educational context in Indonesia. This study uses the Systematic Literature Review (SLR) method with a survey-based quantitative descriptive approach. Data was collected from primary research results published in national and international journals such as Google Scholar, ERIC, and Scopus. The results of this research are from three study focuses related to the use of technology in learning in general, specifically mathematics learning and in the context of increasing pedagogic competence. Where the strategy for increasing teacher competence in applying technology in the classroom is training in the form of activities in the form of training in the use of learning methods, skills training in choosing suitable media, and training in media technology development.